Early Childhood Studies : An holistic introduction - Taylor, Jayne, 1957-; Woods, Margaret, 1943- (London : Hodder Arnold, 2005)
This text is aimed at students studying early childhood as a component of an academic course. Aspects of growth, social provision, psychology, nutrition, health and the law are explored in relation to child development.
Previous ed.: London: Arnold, 1998.
Includes bibliographical references and index.
Keywords: Child development; Child care; Child Care